Strategi Peningkatan Kinerja Pegawai pada Sub Bagian Umum dan Kepegawaian di Kantor Kecamatan Rowokangkung - Eliza, Nova Dewi; Sobri, Wardatuz; Herzegovina, Rani Nurul Laili (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
(Strategies for Improving Employee Performance in the General Affairs and Personnel Subdivision at the Rowokangkung Subdistrict Office) Improving employee performance is a crucial element in efforts to improve the quality of public services at the sub-district office. This study aims to identify and formulate effective strategies to improve employee performance in the general and personnel sub-sections at the Rowokangkung Sub-district Office. The method used in this study is a qualitative approach through in-depth interviews, observation, and analysis of relevant documents. The objectives of the study are to identify steps that can be taken to create a work culture, to identify factors that hinder employee performance, and to identify strategies for improving employee performance in the general affairs and human resources sections of the Rowokangkung subdistrict office. The results of the study indicate that there are several key areas that require attention, including the most significant obstacles: infrastructure, employee competency development, and motivation enhancement. The recommended strategies include continuous training and development, the implementation of a transparent and fair performance evaluation system, and incentive programs to increase motivation and job satisfaction. The implementation of these strategies is expected to improve operational efficiency and effectiveness, as well as enhance the quality of services provided to the community in Rowokangkung Subdistrict. This study makes a significant contribution to designing strategies focused on improving employee performance in the public sector. Well-performing office staff will support the effective and efficient achievement of objectives, thereby accelerating the implementation of activities at the sub-district office. Abstrak Peningkatan kinerja pegawai merupakan elemen krusial dalam upaya peningkatan kualitas pelayanan publik di kantor kecamatan. Penelitian ini bertujuan untuk mengidentifikasi dan merumuskan strategi yang efektif untuk meningkatkan kinerja pegawai pada sub bagian umum dan kepegawaian di kantor Kecamatan Rowokangkung. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif melalui wawancara mendalam, observasi, dan analisis dokumen terkait. Tujuan penelitian yaitu untuk mengetahui langkah-langkah yang dapat diambil untuk menciptakan budaya kerja, untuk mengetahui faktor yang menghambat kinerja pegawai dan mengetahui strategi peningkatan kinerja pegawai pada sub bagian umum dan kepegawaian di kantor kecamatan Rowokangkung. Hasil penelitian menunjukkan bahwa terdapat beberapa kunci yang memerlukan perhatian, termasuk hal yang paling menghambat ialah sarana dan prasarana, pengembangan kompetensi pegawai, dan peningkatan motivasi. Strategi yang di rekomendasikan meliputi pelatihan dan pengembangan berkelanjutan, penerapan sistem evaluasi kinerja yang transparan dan adil, program insentif untuk meningkatkan motivasi dan kepuasan kerja. Implementasi strategi ini diharapkan dapat memperbaiki efisiensi dan efektivitas operasional, serta meningkatkan kualitas pelayanan yang diberikan kepada masyarakat di kecamatan Rowokangkung. Penelitian ini memberikan kontribusi signifikan dalam merancang strategi yang berfokus pada peningkatan kinerja pegawai di sektor publik. Pegawai kantor yang baik akan mendukung tercapainya tujuan secara efektif dan efisien akan menciptakan percepatan pelaksanaan kegiatan di kantor kecamatan.